« Je vous laisse vous habiller. Habillez-vous ! » - Anca-Cristina Sterie; Anne-Sylvie Horlacher; Fanny Bovey (Revue d'anthropologie des connaissances, 2025)
More than two-thirds of nursing home residents in Switzerland live with neurocognitive disorders. The symptoms associated with these diagnoses exacerbate their dependency in daily activities and hinder their communication skills. This paper explores how healthcare assistants support a resident during her intimate dressing routines, in ways that align with a care-centered approach. In an exploratory way, we analyze the resources healthcare assistants employ to engage the resident in the activity of putting on her bra, based on three video-recorded sequences involving one resident. Using multimodal interaction analysis, the paper highlights the verbal and non-verbal resources healthcare professionals mobilize, including their use of objects, bodies, and spatial arrangements. Additionally, it underscores the role of small talk in fostering shared understanding and facilitating the collaborative accomplishment of the activity.